Lighting control of LEDs considering ambient sound variations to meet the requirements of smart cities. (September 2022) - Kalani, Mohammad Javad; Kalani, Mahdi; Salay Naderi, Mehdi; Gharehpetian, Gevork B.
Highlights: Considering the human factor in the performance of lighting systems. Introducing a greater degree of intelligence than traditional approaches by integrating light and sound in compliance with smart city requirements. An operating method for application in various indoor and outdoor environments. A cost-effective solution with decreased operational expenses. Abstract: This study provides an innovative solution by including sound levels in the energy management of light-emitting diodes (LEDs). At the same time, this method increases the accuracy of individuals' decisions regarding the environmental parameters of light and sound. The introduced system determines the environment's activity level using sound sensors. By applying this strategy, the amount of light and the energy consumption of LED light sources is restricted under conditions where no activity occurs in the environment or the level of the performed activity is limited. The results of system simulation and implementation demonstrate the effectiveness of this technique. According to the findings, this method reduces energy consumption by more than 40% in the stated scenario when environmental activity is reduced. This approach is recommended as an innovative solution for the energy management of LED light sources to satisfy users' requirements in smart cities.